Effects of two juvenile hormone analogues, fenoxycarb and merhoprene, on the ant Paratrechina fulva (Mayr) - CHACÓN DE ULLOA, PATRICIA; BAENA, MARTHA L.; ALDANA, ROSA C. (Revista Colombiana de Entomología, 1994)
The preliminary results about the effects of the juvenile hormone analogs, fenoxycarb, and methoprene, on the ant Paratrechina fulva (Mayr) an introduced species in Colombia are presented. Monogynous colonies treated during the fourth week in the laboratory, presented a significant reduction in size six weeks after treatment. This reduction was the result of worker mortality and a decrease in egg production by the queens.